1972
DOI: 10.1021/jf60182a048
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone photodecomposition

Abstract: The metallic dialkyldithiocarbamates have been shown to exhibit inhibitory effects on certain enzyme systems (Thorn and Ludwig, 1962; Dailey et al., 1969). In addition, the results of this study indicate that in any determination of the biological effects of ethyl selenac, the presence of thiuram disulfide, selenite, and diethyldithiocarbamate must be considered. Selenite ion is known to inhibit several enzyme systems (Rosenfeld and Beath, 1964). TETD, also known as Antabuse or Disulfiram, is not only a rubbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…However, rotenone has a serious limitation to its widespread usage due to its susceptibility towards ultraviolet rays or solar irradiation. Owing to rotenone's high photolability, either breaking down or isomerizing in the presence of sunlight will decrease its bioactivities under field conditions, resulting in poor persistence in the environment and inadequate field performance [5]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, rotenone has a serious limitation to its widespread usage due to its susceptibility towards ultraviolet rays or solar irradiation. Owing to rotenone's high photolability, either breaking down or isomerizing in the presence of sunlight will decrease its bioactivities under field conditions, resulting in poor persistence in the environment and inadequate field performance [5]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the plant secondary metabolites are thermal resistance, this finding has proven that rotenone is one of the metabolites that is very sensitive to prolong heat exposure and it needs to be extracted and operated below 40 o C. The reason behind this is that when rotenone is exposed to light, air and heat, it decomposes into dihydrorotenone and water resulting in non-insecticidal bio-active compounds (Cavoski et al 2007;Schnick 1974). Another study by Cheng et al (1972), using photo-degradation, identified that rotenone decomposed to at least 20 degradation products, most of which were rotenoids (rotenone and its derivatives). They reported that only one product, 6aβ, 12αβ-rotenolone, was toxic.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike some other pesticides, rotenone is not environmentally persistent and degrades rapidly under natural conditions. Rotenone powders lose much of their toxicity within weeks without careful storage and must be protected from air, light and alkali, at temperatures not exceeding 25 o C. Solutions of rotenone in organic solvent, when exposed to light and air, become successively yellow, orange and finally deep red due to oxidation (Cheng et al 1972). …”
Section: Sources and Impuritiesmentioning
confidence: 99%
“…Containers of powdered formulations rapidly lose their activity when open to the air and should remain sealed whenever possible. Liquid formulations are more stable so long as they are stored sealed and kept in a cool dark place (Cheng et al 1972). …”
Section: E N V I R O N M E N T a L P E R S I S T E N C Ementioning
confidence: 99%